Posidonia oceanica (L.) Delile at ItsWesternmost Biogeographical Limit (Northwestern Alboran Sea): Meadow Features and Plant Phenology - Mateo-Ramírez, Ángel; Marina, Pablo; Martín-Arjona, Alejandro; Bañares-España, Elena; García-Raso, José Enrique; Rueda, José L.; Urra, Javier (MDPI, 2023)
Meadows of the seagrass Posidonia oceanica inhabit most infralittoral bottoms of the Mediterranean Sea and are considered one of the main climax stages of the infralittoral environment. This seagrass has its western distributional limit along the coast of the Alboran Sea. Taking into account the decline of P. oceanica meadows and the global scenario of ocean warming, it becomes essential to know the structure, temporal dynamics, sexual reproduction and conservation status of this seagrass, across its geographical distribution, including the distribution boundaries where the meadows withstand limiting environmental conditions. In the present work, we studied the structure, phenology and flowering events of four P. oceanica meadows located in the northwestern Alboran Sea (close to the Strait of Gibraltar). Results indicate a decreasing trend of patch size, bathymetric range and number of leaves per shoot towards the Strait (and the Atlantic Ocean), as well as an increasing trend of shoot density and leaf height. Phenological parameters of the northwestern Alboran Sea P. oceanica meadows presented temporal dynamics similar to meadows from other locations within the biogeographical distribution of this seagrass, with similar or even less annual variability in the former. Although most of the studied P. oceanica meadows seem to present a good health status (BiPo index ~0.6) with high shoot densities and some flowering events, some of them showed evidence of regression.
Keywords: Biología marina; Botánica - Investigación; Seagrass; Mediterranean Sea; Atlantic influence; Life cycle; Infralittoral; Habitat regression